Pengaruh Komunikasi Interpersonal Pustakawan terhadap Kepuasan Pemustaka di Perpustakaan Era Digital (Studi Kasus di Poltekkes Kemenkes Padang) - Putri, Andini Winata; Nabila, Jeihan (ARZUSIN, 2024)
The purpose of this study was to determine (1) describe the interpersonal communication of librarians in the Library of Poltekkes Kemenkes Padang. (2) describe the level of user satisfaction at the Poltekkes Kemenkes Padang Library. (3) describe the effect of librarian interpersonal communication on the level of library satisfaction at the Poltekkes Kemenkes Padang Library in the digital era. This research is a type of quantitative research with descriptive methods, data obtained through distributing questionnaires at the Poltekkes Kemenkes Padang Library. The population in this study was visitor data from January to December 2022 with a sample size of 99 respondents. Sampling is determined based on the Simple Random Sampling Technique which is a sampling technique that is carried out randomly without regard to the strata in the population. The results of this study are (1) interpersonal communication of librarians at the Poltekkes Kemenkes Padang Library is classified as high with an average value of 3.07 on a good interval scale. (2) user satisfaction at the Poltekkes Kemenkes Padang Library is high with an average of 3.19 on a good interval scale. (3) Librarian interpersonal communication affects library satisfaction at the Poltekkes Kemenkes Padang Library, where the Fhitung value (39.747)> Ftabel (3.94) at a significant level of 5% which states that there is a significant influence between librarian interpersonal communication on library satisfaction at the Poltekkes Kemenkes Padang Library.